Pengaruh Pendidikan Seksual untuk Anak Usia Dini terhadap Upaya Pencegahan Kekerasan Seksual di Tk Keling Betuah Desa Sentabai - Suryani Suryani; Sofia Afritasari (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Sexual violence that occurs against children can have a major impact on their survival. The aim of this research is to determine the effect of sexual education for early childhood on efforts to prevent sexual violence in Keling Betuah Kindergarten, Sentabai Village. The type of research used was quasi-experimental using a one group pre and post test design, with a sample of 30 kindergarten children taken by purposive sampling. This research uses a research instrument using the concept of underwear rules applied through PANTS. The research was carried out using leaflets and videos. The research was conducted involving parents. Data were processed univariately and bivariately using Wilcoxon test analysis. The results of the research show that there is an influence of sexual education for early childhood on efforts to prevent sexual violence in Keling Betuah Kindergarten, Sentabai Village.